Citrus BMP Implementation in Florida's Gulf Citrus Production Area: Water, Sediment, and Aquatic Weeds - Sanjay Shukla; Robert E. Rouse; S. S. Shukla; Edward A. Hanlon; Kenneth Portier; Thomas A. Obreza (EDIS)
Circular 1497, a 12-page publication by S. Shukla, R. E. Rouse, S. S. Shukla, E. A. Hanlon, K. Portier, and T. A. Obreza, describes a survey conducted by the authors in cooperation with the Gulf Citrus Growers Association (GCGA) and the Florida Department of Agriculture and Consumer Services (FDCAS) to quantify the current level of Best Management Practice (BMP) implementation and to identify BMPs that might be adopted if a cost-share program was available. It discusses the findings regarding water, sediment, and aquatic weed BMPs. Includes tables, additional references, and the survey questions. Published by the UF Department of Agricultural and Biological Engineering, October 2006.